Advanced anaerobic processes to enhance waste activated sludge stabilization - Braguglia, C M (Water science and technology : a journal of the International Association on Water Pollution Research, 2014)
The requirement for enhanced stabilization processes to obtain a more stable, pathogen-free sludge for agricultural use is an increasing challenge to comply with in the waste hierarchy. With this in mind, the Routes European project ('Novel processing routes for effective sewage sludge management') is addressed to assess innovative solutions with the aim of maximizing sludge quality and biological stability. In order to increase anaerobic stabilization performances, the sequential anerobic/aerobic process and the thermophilic digestion process, with or without integration of the thermal hydrolysis pre-treatment, were investigated as regards the effect on sludge stabilization, dewaterability and digestion performances. Thermal pre-treatment improved anaerobic digestion in terms of volatile solids reduction and biogas production, but digestate dewaterability worsened. Fluorescence in situ hybridization (FISH) quantification showed an increase of methanogens consistent with the increase of biogas produced. The aerobic post-treatment after mesophilic digestion had a beneficial effect on dewaterability and stability of the digested sludge even if was with a reduction of the potential energy recovery